2018
DOI: 10.1371/journal.pone.0206905
|View full text |Cite
|
Sign up to set email alerts
|

Validation and psychometric properties of the Russian version of the Touch Experiences and Attitudes Questionnaire (TEAQ-37 Rus)

Abstract: It has been demonstrated that nurturing and affiliative touch is essential for human emotional and physical well-being throughout our entire life. Within the last 30 years a system of low-threshold mechanosensitive C fibers innervating the hairy skin was discovered and described; this system is hypothesized to represent the neurobiological substrate for the affective and rewarding properties of touch. This discovery opens new perspectives for multidisciplinary research of the role of affiliative social touch i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 53 publications
(58 reference statements)
4
33
0
Order By: Relevance
“…For example, Sailer and Ackerley (2017) found that adults self-reporting a low frequency of social tactile interactions rated CT optimal touch as less pleasant than a group who reported frequent touch. However, it seems unlikely current levels of touch are driving our effects because, using our previously validated self-report measure ( Trotter et al, 2018a , b ), we found no difference between the two groups in their current experiences of either intimate touch or tactile interactions with friends and family.…”
Section: Discussionmentioning
confidence: 69%
“…For example, Sailer and Ackerley (2017) found that adults self-reporting a low frequency of social tactile interactions rated CT optimal touch as less pleasant than a group who reported frequent touch. However, it seems unlikely current levels of touch are driving our effects because, using our previously validated self-report measure ( Trotter et al, 2018a , b ), we found no difference between the two groups in their current experiences of either intimate touch or tactile interactions with friends and family.…”
Section: Discussionmentioning
confidence: 69%
“…A mean score was calculated for each of the six subscales; friends and family touch (FFT) (11 items), current intimate touch (CIT) (14 items), childhood touch (ChT) (9 items), attitude to self-care (ASC) (5 items), attitude to intimate touch (AIT) (13 items) and attitude to unfamiliar touch (AUT) (5 items), with negatively worded questions reversed scored. The TEAQ questionnaire was found to have a good internal consistency with Cronbach α= 0.78-0.92 [52,66]. For this investigation, we were particularly interested on the TEAQ Attitude to intimate touch (AIT) subscale because previous investigations suggest that AN patients experience intimate stimuli with lower valence and dominance than healthy controls [53].…”
Section: Touch Experiences and Attitudes Questionnairementioning
confidence: 99%
“…Moreover, we chose to display videos showing only males delivering touch and females receiving touch as generally males appear to initiate touch more than females do [67,68]. All videos were taken from a database of previously standardised video clips [66]. Touch was delivered across five different body regions: non-CT-innervated body site i.e., palm vs. CT-innervated body sites i.e., back, ventral forearm, cheek and upper arm) with 3 different stroking velocities: static (0 cm/s), slow (5cm/s) and fast (30 cm/s).…”
Section: Self-and Other-directed Affective Touch Video Clipsmentioning
confidence: 99%
See 2 more Smart Citations